Pengurusan sistem sungai bagi tujuan pengangkutan - Kong, Kim Fong (2004)
Inland waterway transportation system or IWTS is a major form of transport system and widely used for commercial transportation and recreational especially in some countries in Europe and United States of America. Development of inland waterways for transportation requires one management system for the purpose of administrating and controlling. In this context, authority plays a major role in various aspect of management. This study will identify some major problem in the management system of IWTS in Malaysia. At this stage, there is no authority responsible specifically this sector in Malaysia. This problem poses a threat to the potential of inland waterway in Malaysia to be developed for transportation and IWTS could not compete with other mode of transport. This situation also cause various problem such as overlapping of authority which will lead to waste of time, manpower, capital and create conflict between various parties which are different purpose involved in the waterways usage. In this study, some management models of inland waterways for transportation will be studied especially models from country with well established IWTS. Study will be focused on some aspects such as the role and power of the authority, management methods as well as government policy. Finally, this project will produce a general model for managing inland waterways transport (IWT) system for Malaysia. This model could be used as reference and guideline for future research for various parties interested in this field.